Outcome of Long-Term Corticosteroid Treatment in Duchenne Muscular Dystrophy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The clinical orthopedic effects of chronic daily corticosteroid treatment were evaluated by chart review in boys with genetically confirmed Duchenne muscular dystrophy (DMD) followed at the Ohio State University Muscular Dystrophy Clinic between 2000 and 2003.